Kinetic and thermodynamic Studies Of Alanine Aminopeptidase(AAP) Isoenzymes I,II Partially Purified From Patient's Urine With Urinary Tract Cancer (Baghdad Science Journal, 2014)
The activity of Alanine aminopeptidase( AAP ) was measured in the urine of healthy and urinary tract cancer patients , the results showed higher activity of (AAP) in patients compared to healthy . AAP was Purified from the urine of healthy and patients with urinary tract cancer by dialysis and gel filtration (Sephadex G – 50) and two isoenzymes of (AAP) were separated from urine by using ion-exchang resin (DEAE – Sephadex A – 50 ) in previous study.The kinetics studies showed that both isoenzymes I and II obeyed Michaelis – Menton equation . with optimal concentration of alanine-4-nitroanilide as substrate for isoenzymes I and II which was (2 x 10-3 mol/L ). The two isoenzymes obeyed Arrhenius equation up two 37° C and their Ea and Q10 constants were determined . The binding of alanine-4-nitroanilide by two isoenzymes I , II were studied and the kinetic constant ( k+1 , k-1 , Ka , Ks ) were indicated that the reaction was first order at 37° C .Thermodynamic parameters of the standard state ( ?G°, ?H° , ?S° ) and the transition state ( ?G*, ?H* , ?S* ) were determined by using Vant Hoff and Arrhenius equations.